The Implementation and Transformation of Kulintang Melodies in the Rite of Mak Kamalun: A Minimalist Composition Analysis - Kadafi, Fadel; HR, Hafif; Anggara, Rama (Scoring: Journal of Film Music, 2025)
The fusion of traditional Indonesian musical material with modern Western aesthetics has become a field of exploration in musical composition. Kulintang, as a musical system from the Mamasa people (West Toraja/West Sulawesi) and the Maranao people of the Philippines, provides a rich source of melodic and rhythmic structures that have not been widely explored within a minimalist musical framework. This article aims to analyze the implementation and transformation of kulintang melodies in the orchestral composition "Ritus Mak Kamalun," using an analytical approach to the minimalist musical techniques used. This study uses a descriptive-analytical method of music analysis, combining the theory of motif transformation (Straus, 2016) and the principles of minimalist music (Potter, 2002; Johnson, 1989). Primary data consists of scores and audio recordings of Ritus Mak Kamalun, and secondary data consists of ethnomusicological literature on kulintang. The analysis shows that Kulintang melodies are not simply implemented as excerpts, but are systematically transformed through (1) phase shifts and additive processing of short patterns (cells), (2) repetitions with microvariations of typical Kulintang intervals (such as the minor second and quart), and (3) recontextualization of pentatonic melodic patterns into an expanded tonal system. These transformations produce organically evolving structures, retaining the "soul" of traditional motifs while operating within a minimalist logic. The Mak Kamalun ritual demonstrates that ethnic material can function as a generative core in minimalist compositions, not merely as additional color. This study contributes to an analytical model for integrating traditional material into modern musical forms, as well as enriching the understanding of Kulintang's potential beyond its traditional ritual context.Keywords: Kulintang, minimalist music, compositional analysis, motif transformation, contemporary Indonesian music, applied ethnomusicology.